Strategi Sekolah dalam Mencegah Pergaulan Bebas pada Remaja di MAN 1 Samarinda - Rahman, Abdur (el Buhuth: Borneo Journal of Islamic Studies, 2018)
The strategies of the school in preventing promiscuity in adolescents at MAN 1 Samarinda are by holding learning that emphasizes courtesy towards other and environment, communicating with students, optimizing teacher’s roles as the role model and the motivator, and educating to be devoted to parents. This research aims to find out the efforts and strategies of the school in preventing promiscuity in adolescents. This research was a descriptive qualitative research by collecting data through interviews, observation, and documentation. The data sources were the principal, guidance and counseling teachers, faith and moral teachers, and the vice principal for student affairs. The data analysis used data reduction, data presentation and verification. The result of this research are 1) strengthening the school regulation, 2) Installing CCTV, 3) Implementing the incidental inspection program, 4) Providing more extracurriculars related to religion, 5) Holding social works, 6) cooperating with the government institutions. Repressive efforts were done by implementing home visit, where the teacher visits students’ houses when students experiencing problems, as a specific handling approach. The curative strategy for students who violate the school regulation or are naughty is by implementing specific guidance involving parents and spiritual-mental guidance.